The removal of toxic anions from wastewater using electrospun nanofibers - Moronkola, Bridget Adekemi (Rhodes University, Faculty of Science, Department of Chemistry, 2016)
The presence of arsenic and phosphate in waters, especially wastewater, has become a worldwide problem even till the present time. The current regulation of drinking standard water has become more stringent and requires arsenic content to be reduced to a few parts per billion. Nevertheless, phosphorous pollution, known as the eutrophication, is regarded as one of the main causes of water quality deterioration. Hence, the decontamination of phosphorous from aqueous solutions is of importance for eutrophication control and phosphorous recovery. Efforts are being made to remove these contaminants, arsenic (v) and phosphate from wastewater using low cost adsorbents. In the present study, removal of arsenic(v) and phosphate from wastewater using two novel fabricated sorbent materials; polyvinylmethylketone functionalized 2-amino4,6-dihydroxylpyrimidine (APPMKNFs) prepared via a Schiff base condensation reaction and aminated polyvinylbenzylchloride (PVBC) prepared through a substitution reaction and then quaternized using three alkyl groups (R' = CH₃, C₂H₅ and C₃H₇) were investigated. The experiments were carried out in batch and solid phase extraction mode. Preliminary experiments were done with series of four sorbent materials (APPMKNFs, R' = CH₃, C₂H₅ and C₃H₇) in order to find out a suitable and low cost adsorbents for the effective removal of arsenic (v) and phosphate. The best sorbent materials were obtained after the optimization and preparation experiments. The APPMKNFs and R' = CH₃ were effective for arsenic (v) and phosphate removal from wastewater. The effect of pH, initial sorbate concentration, amount of sorbent, effect of co-exisiting anions and the reusability in batch and solid phase extraction mode were also investigated. From the experiment conducted, the pH shows a decisive factor on arsenic and phosphate removal. Analysis of adsorbent dosage, Kinetic studies and co-existing anions were carried out in order to evaluate sorption parameters. The adsorption isotherms were well fitted by Langmuir than Freundlch isotherm for (APPMKNFs). And more...
Keywords: Uncatalogued